Stimulator of Interferon Genes Deficiency in Acute Exacerbation of Idiopathic Pulmonary Fibrosis - Qiu, Hui; Weng, Dong; Chen, Tao; Shen, Li; Chen, Shan-Shan; Wei, Ya-Ru; Wu, Qin; Zhao, Meng-Meng; Li, Qiu-Hong; Hu, Yang; Zhang, Yuan; Zhou, Ying; et al. (Frontiers in Immunology, 2017)
The stimulator of interferon genes (STING) is a key adaptor protein mediating innate immune defense against DNA viruses. To investigate the role of STING in acute exacerbation of idiopathic pulmonary fibrosis (AE-IPF), we isolated primary peripheral-blood mononuclear cells (PBMCs) from patients and healthy controls (HCs). Raw264.7 and A549 cells were infected with herpes simplex virus type 1(HSV-1). Mice with bleomycin-induced lung fibrosis were infected with HSV-1 to stimulate acute exacerbation of the lung fibrosis. Global gene expression profiling revealed a substantial down-regulation of interferon-regulated genes (downstream of STING) in the AE-IPF group compared with the HC and stable IPF groups. The PBMCs of the AE-IPF group showed significantly reduced STING protein levels, increased levels of endoplasmic reticulum (ER) stress markers, and elevated apoptosis. HSV-1 infection decreased STING expression and stimulated the ER stress pathways in Raw264.7 and A549 cells in a time- and dose-dependent manner. HSV-1 infection exacerbated the bleomycin-induced lung injury in mice. In the primary bone-marrow-derived macrophages of mice treated with bleomycin and HSV-1, STING protein expression was substantially reduced; ER stress was stimulated. Tauroursodeoxycholic acid, a known inhibitor of ER stress, partially reversed those HSV-1-mediated adverse effects in mice with bleomycin-induced lung injury. STING levels in PBMCs increased after treatment in patients showing improvement but remained at low levels in patients with deterioration. Viral infection may trigger ER stress, resulting in STING deficiency and AE-IPF onset.